Functional diversity of supragranular GABAergic neurons in the barrel cortex - Gentet, Luc J. (Frontiers in Neural Circuits, 2012)
Although the neocortex forms a distributed system comprised of several functional areas, its vertical columnar organization is largely conserved across areas and species, suggesting the existence of a canonical neocortical microcircuit. In order to elucidate the principles governing the organization of such a cortical diagram, a detailed understanding of the dynamics binding different types of cortical neurons into a coherent algorithm is essential. Within this complex circuitry, GABAergic interneurons, while forming approximately only 15–20% of all cortical neurons, appear critical in maintaining a dynamic balance between excitation and inhibition. Despite their importance, cortical GABAergic neurons have not been extensively studied in vivo and their precise role in shaping the local microcircuit sensory response still remains to be determined. Their paucity, combined with their molecular, anatomical, and physiological diversity, has made it difficult to even establish a consensual nomenclature. However, recent technological advances in microscopy and mouse genetics have fostered a renewed interest in neocortical interneurons by putting them within “visible” reach of experimenters. The anatomically well-defined whisker-to-barrel pathway of the rodent is particularly amenable to studies attempting to link cortical circuit dynamics to behavior. To each whisker corresponds a discrete cortical unit equivalent to a single column, specialized in the encoding and processing of the sensory information it receives. In this review, we will focus on the functional role that each subtype of supragranular GABAergic neuron embedded within such a single neocortical unit may play in shaping the dynamics of the local circuit during somatosensory integration.